Do grapes produce blood? A problematic metaphor in biblical texts - Dr. Mark Wilson (Pharos Journal of Theology, 2022)
This article focuses on a metaphor often misunderstood and mistranslated in biblical texts. Relevant texts in the Old Testament/Jewish Bible and the Deuterocanonicals are surveyed first, and fresh translations and interpretations of these are then offered. Several texts utilizing this same metaphor in the New Testament are then discussed. The article proposes that Jesus and John understood the metaphorical use of blood as wine/juice from Jewish literature and thus used it effectively in their verbal and written discourse. The failure to understand this metaphor has produced an overly literal interpretation both in the Gospels and in Revelation. The failure to understand the metaphor in the harvest imagery of Revelation, particularly in 14:20, has contributed to the perception that the Apocalypse endorses extreme violence. The article proposes a different translation of the verse based on the conclusion that grapes do not produce blood.